Slow Community Development Enhances Abiotic Limitation of Benthic Community Structure in a High Arctic Kelp Bed - Bonsell, Christina; Dunton, Kenneth H. (Frontiers in Marine Science, 2021)
Seasonal hydrographic fluctuations may impart strong abiotic control on community structure in nearshore Arctic ecosystems, but the effects may be overcome by propagule delivery and recruitment. We compared spatial differences in benthic community structure to environmental factors (temperature, salinity, current speed, underwater light) and static habitat attributes (depth, distance from river inputs) in a shallow High Arctic kelp bed in the Beaufort Sea. Spatial and temporal patterns of recruitment and community development were observed to assess the timescale and trajectory of community development. Foliose red algae (47-79%), prostrate kelps (2-19%), and crustose coralline algae (0-19%) dominated the epilithic community. Strong spatial distinctions among sites included a positive correlation between cover by crustose coralline algae and distance to river inputs. We found no significant relationships between environmental factors and functional groups. Differences between early-successional and established benthic communities indicated that slow growth rates result in prolonged community development, augmented by strong abiotic control over local community structure. Growth and post-recruitment mortality determine crustose coralline algae and invertebrate prevalence in the established community, while kelp seem to be largely recruitment-limited. On scales >1 m, community structure depends on bathymetry and exposure to freshwater intrusion. Colonization rates (means of 3.3-69.9 ind. 100 cm-1 year-1 per site) were much lower than studies in other Arctic kelp habitats, and likely reflect the nature of a truly High Arctic environment. Our results suggest that community development in the nearshore Beaufort Sea occurs over decades, and is affected by combinations of recruitment limitation, primary disturbance, and seasonal abiotic stressors. While seasonality exerts strong influence on Arctic systems, static habitat characteristics connect seasonal variability to benthic ecosystem structure by integrating abiotic conditions over timescales longer than most ecological studies.